Innovations in maternal health : case studies from India - Satia, Jay K. (Sage Publications, 2014)
Innovations in Maternal Health presents a compilation of twenty-three innovations from the area of Maternal and Newborn Health. These innovations have been written in the case-study style for teaching, which will be beneficial for capacity building initiatives for health-care professionals. These descriptive cases cover innovative programmes, initiatives and technologies implemented in India. Each case is complemented by a documentary film provided in the accompanying DVD. <div style=""te